Governing cryptocurrencies through forward guidance? - Matthias Goldmann; Grygoriy Pustovit (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
While the debate about the needs and merits of cryptocurrency regulation is ongoing, the unprecedented price hikes of cryptocurrencies towards the end of 2017 triggered a somewhat unexpected sort of regulation in the form of public statements by governments and financial supervisors. It kicked in rather quickly and turned out to be much more effective than imagined. These interventions can be identified as one of the main factors that drove asset prices down, thereby preventing destabilizing bubbles. The experience of the supervisory response to the cryptocurrency bubble of the past months keeps important insights for any prospective regulation of cryptocurrencies. First, public statements are a highly effective regulatory tool in the short term as they manage market expectations, a fact which is well-known as forward guidance in monetary policy. So far, the legal framework in the EU takes insufficient account of the regulatory role of public statements. Second, regulation needs to keep up with the incredible speed of fintech innovations. Some regulators addressed the challenge by adopting a "sandbox" approach. However, the "sandbox" approach clearly calls for international cooperation. To achieve a balance between safety and innovation, international cooperation should emulate the experimental character of sandboxes. One could conceive of a "sandbox for regulators", an arrangement which would facilitate the exchange of information on regulatory initiatives among authorities but also the coordination of communication and forward guidance.
urn:nbn:de:hebis:30:3-466834
Keywords: 330; cryptocurrencies; blockchain; distributed ledger technology; regulation; forward guidance